The performance art and the aesthetics in merleau-ponty: : disruption, frontier and expression (Palíndromo, 2021)
This article aims to discuss the expressive phenomenon of Performance Art, based on the as-sumptions of a theory of aesthetic expression present in Merleau-Ponty’s philosophy. At first the paper analyses the notions of rupture and frontier present in the Performance Art, in the light of the phenomenological method used by Merleau-Ponty, the épokhe; and then, it intends to approach the analysis of Merleau-Ponty’s aesthetic texts, from the perspective of a theory of style, and the expressive phenomenon present in the Performance Art. It is found that it is in the analysis of the creative power of re-creating the world, identified in Cézanne’s painting, languageand enigma of vision, that Merleau-Ponty develops an aesthetic theory of style. The notion of style emerges in his essays as the capacity of intertwining a personal dimension with a universal dimension, or even as an expression of being with the world. Performance Art as a frontier art, hy-brid in languages and founded on the here and now of embodied embodiment, conceives in its activity the expressive phenomenon present in Merleau-Ponty’s theory of aesthetic expression.
Keywords: Performance Art.; Merleau-Ponty.; Expression.; Frontier.; Disruption.